2021
DOI: 10.1038/s41433-021-01449-6
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic endophthalmitis caused by streptococcus species in preschool children: clinical features, antibiotic susceptibilities and outcomes

Abstract: Background/Objectives Streptococcus is a common cause of post-traumatic endophthalmitis in children. This study aimed to analyse the clinical features, antibiotic susceptibilities and outcomes of traumatic endophthalmitis caused by streptococcus in preschool children. Subjects/Methods Patients aged ≤6 years with traumatic streptococcal endophthalmitis seen at Zhongshan Ophthalmic Center between January 2013 and December 2018 were included in this retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…It was consistent with previous reports. 3,8,[31][32][33][34] In our study, the pathogen identified was concordant in seven of 10 culture-positive cases. Discordance between mNGS and culture was also reported in the literature.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…It was consistent with previous reports. 3,8,[31][32][33][34] In our study, the pathogen identified was concordant in seven of 10 culture-positive cases. Discordance between mNGS and culture was also reported in the literature.…”
Section: Discussionsupporting
confidence: 63%
“…E ndophthalmitis, one of the most severe ophthalmic emergencies, requires urgent treatment to save the vision or salvage the integrity of the eye. 1,2 The common causes of endophthalmitis include trauma, 3,4 intraocular surgery, 5,6 or endogenous dissemination. 7,8 Endophthalmitis may be caused by bacteria 8 or by fungi.…”
mentioning
confidence: 99%
“…The most commonly identified organisms in our study were coagulase-negative staphylococci and S. aureus, comprising 50% of the isolates, as seen in other studies. 3,8,15 Culture-positive rates have been reported to range from 44% to 75% in Western studies. 11 Narang et al reported 27% culture positivity from ocular specimens in India.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus spp. are the leading cause of late bleb-related endophthalmitis and a common cause of post-traumatic endophthalmitis [ 15 , 16 ]. They are also frequently implicated after post-cataract surgery, vitrectomy, and intravitreal injection [ 15 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%